The Effect of Tax Revenues, Exports and Imports on Economic Growth: Analysis using Error Correction Model (ECM) - yossinomita (Jurnal Ilmiah Manajemen dan Kewirausahaan (JUMANAGE), 2022)
The purpose of this study is to analyze the effect of tax revenues, exports and imports on economic growth in Indonesia in the long and short term. In this study, secondary data obtained from BPS Indonesia 2000-2019 was used. The analysis used is regression analysis using Error Correction Model (ECM). The tests used in the model are Stationarity Test, R-Square Test, F Test and T Test. The results showed. Tax revenues, exports and imports together have a significant influence on economic growth, both in the long and short term. Where the export variable has a significant effect on economic growth in the long and short term. The tax revenue variable has no effect in the long term, but has a significant effect on economic growth in the short term. Meanwhile, the import variable has no effect on economic growth, both in the long and short term.